BINARY OPPOSITIONS AS THE RESULT OF DECONSTRUCTION ANALYSIS IN THE GOLDFINCH NOVEL BY DONNA TARTT - Cheristine Aprilia; Tomi Arianto (BASIS (Bahasa dan Sastra Inggris), 2021)
This research is aimed to analyse the binary opposition in the “The Goldfinch” novel by Donna Tartt. The problem that analysed in this research focused on binary opposition of major character in the novel. The approach to analysing binary opposition used Derrida's concept, namely the theory of deconstruction by Jacques Derrida which is categorised as a poststructuralist approach. Deconstruction theory is understood as a theory that dismantles existing general views. The concept of binary opposition is directed to analyze the difference between two things which are considered to produce a new perspective and can be accepted by many people. The method used in this research is qualitative descriptive method, namely the author described and analysed existing data. The data is from the quotation of the novel. The result of the research is there are five binary oppositions, they are good – bad, valuable – worthless, honest – dishonest, caring – ignorant, and crowded – silent. The binary oppositions are found in the characters of the story. The characters in the story represent some of the characters of other people in the real world. People's perceptions about certain human characteristics can be explored deeper and have opposite sides.